ASSESSMENT OF HEAVY METAL CONTAMINATIONS OF SOILS FROM DUMP SITES IN JOS METROPOLIS, NORTH CENTRAL NIGERIA (FULafia Journal of Science and Technology, 2020)
A study was carried out to determine the heavy metal contamination of the soils in three refuse dumpsites in Jos metropolis located in Rayfield Resort, Dariye Park and Farin Gada within the Jos-Bukuru Complex of Younger Granite Province of northcentral Nigeria. Six (6) soil samples were collected at depth of 40 cm from the three dumpsites. The soil samples were subjected to X-Ray fluorescence (XRF) analysis to determine the concentrations of heavy metals. The values of heavy metals in the soils from the three dumpsites were foundto be: zirconium (382.537-1045.734 ppm), strontium (54.584-185.030 ppm), uranium (8.496-12.055 ppm), rubidium (60.189-111.280 ppm), thorium (13.305-30.138 ppm), lead (26.790-277.342 ppm), arsenic (7.971- 27.819 ppm), zinc (129.790-734.643 ppm), copper (31.899-247.048 ppm), nickel (42.454-72.670 ppm), iron (22162.547-64319.262 ppm) and manganese (214.146-449.344 ppm).
Keywords: dissolution; leaching; anthropogenic; waste and decomposition